THE INCREASING OF WEST SUMATRA EXPORT IN THE GLOBAL MARKET DURING THE COVID-19 PANDEMIC - Silvy Cory; Sofia Trisni; Putriviola Elian Nasir (Dauliyah: Journal of Islam and International Affairs, 2022)
The international trade sector, especially exports, has become one of the focuses of the Indonesian government, especially the West Sumatra government. West Sumatra's leading export products such as essential oils, CPO, and rubber products have their own markets in the global market. Data from the West Sumatra Central Statistics Agency shows a significant increase in the export value of West Sumatra from the end of 2019 to the final quarter of 2020. This study aims to look at the factors that support the increase in exports of West Sumatra in the global market during the Covid-19 pandemic. To see these factors this study will use the concept of a resource-based paradigm which will focus on internal factors and the contingency paradigm that focuses on external factors of international trade. This research uses qualitative research methods with a descriptive analysis approach. This study found that internal factors of increasing West Sumatra exports, namely West Sumatra government policies that support exports, the experience of local companies, and the performance of these two parties. Meanwhile, internal factors are the conditions of competition between countries in increasing production and the increasing global demand for food and medicinal products.